PENGARUH SOCIAL MEDIA MARKETING DAN BEAUTY INFLEUNCER TERHADAP MINAT BELI PRODUK KOSMETIK WARDAH (STUDI KASUS PADA MAHASISWA UIA) - Pangeran Syarif Abdurrahman Bahasyim; Mela Meilawati (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2023)
The purpose of this study was to determine "The Influence of Social Media Marketing an d Beauty Influencers on Interest in Buying Wardah Cosmetic Products (Case Study of As -Syafi'iyah Islamic University Students) The population in this study were UIA students. The sample in this study used a non-probability sampling technique. Data was collected by distributing questionnaires. The data analysis method used is multiple regression ana lysis, correlation, coefficient of determination, t test and f test. Based on the results of da ta analysis and discussion, partially social media marketing has a significant and positi ve effect on purchase intention with a tcount of 9.119 > ttable 1.988 indicating a signific ance level of 0.000 <0.05, beauty influencers partially have a positive and significant eff ect on purchase intention with a tcount of 11.119 > ttable 1.988 indicating a significance level of 0.000 <0.05. The coefficient of determination (R2) of 0.593 indicates that the in dependent variable (X) is able to partially explain 59.3% of the variation that occurs in the dependent variable (Y), while the remaining 40.7% is influenced by other factors not examined. Based on the results of the f test where Fcount is 73.059 > Ftable 3.09 and a significance level of 0.000 <0.05, it can be concluded that social media marketing and b eauty influencers in the model are feasible to explain the purchase intention variable.